(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
During the Palaeolithic Age-the Early Stone Age-flake tools that could be used like knives were made of stone flakes. These tools can be divided into two, based on the edges of the tool, namely edges that are used directly and edges that have been retouched. A flake tool that has been retouched before being used is known as retouched flake tool. In addition, these two types of stone tools are also known as scrapers. They are named based on their functions because they do not have any particular shape, and are thus called ’amorphous’. Therefore, a classification analysis needs to be carried out to understand the technology produced and its relationship to the function of the tools. This illustrates the strategy of adaptation among the Palaeolithic society in the Early Stone Age. This study will also answer the issue on environmental exploitation such as how this nomadic society used its environment to produce stone tools. Moreover, the classification study will also encourage us to know more about the organization of technology and adaptation strategies of the Palaeolithic societies in Malaysia. Keywords: flake tools, amorphous, classification, technology, retouch